The birds of the Potter Peninsula, King George Island, South Shetland Islands, Antarctica, 1965-1998 - Hahn, Steffen; Peter, H.-U.; Quillfeldt, Petra; Reinhardt, K.; Justus Liebig University Giessen (My University, 1998)
Records of breeding and non-breeding birds of the Potter Peninsula, King George Island, South Shetland Islands, Antarctica, part of which is a Site of Special Scientific Interest (SSSI), are reviewed from 1965 to 1998. The numbers of breeding pairs of skuas Catharacta spp. (max. 85) and Wilson’s Storm Petrels Oceanites oceanicus (1400–2300) are much higher than previously assumed. Breeding is confirmed for the Black-bellied Storm Petrel Fregetta tropica. Pintado or Cape Petrel Daption capense and Imperial or Blue-eyed Cormorant Phalacrocorax atriceps are at least occasional breeders. Seven non-breeding taxa are added to the bird list of Potter Peninsula, now totalling 27 taxa, of which 13 species have been recorded breeding. Differences between previously published records and our own surveys cannot sufficiently be explained by temporal changes and reflect methodological problems with the latter. The boundaries of the SSSI should be enlarged to include the storm petrel populations of Three Brothers Hill.
Keywords: ddc:570